Review of Siyasah Dauliyah on the Immigration Document Control System for Indonesian School Students in Kota Kinabalu by the Consulate General of the Republic of Indonesia Kota Kinabalu Sabah Malaysia - Atqiyatun Nisa, Syifa; Asro, M.; Fahrul Rizal, Lutfi (Dinasti Research, 2024)
This research aims to conduct an in-depth review of legal supervision of immigration documents of Indonesian School students in Kota Kinabalu by the Consulate General of the Republic of Indonesia in Kota Kinabalu Sabah Malaysia through the perspective of Siyasah Dauliyah. This study uses an empirical legal method by looking at the legal reality that exists in society which includes legal identification of legal effectiveness. The data collected were analyzed descriptively. The results of the study indicate that supervision of immigration documents of Indonesian citizens residing in foreign countries has been regulated in Law Number 6 of 2011 concerning Immigration. This law regulates the implementation and function of immigration both domestically and as representatives abroad. This study also identified several obstacles in the supervision of immigration documents of Indonesian citizens residing in Malaysia. These obstacles include understanding the rights and obligations of living in other countries, lack of awareness of the importance of travel documents or residence permits in other countries, and criminal provisions for not having complete immigration documents. That supervision of immigration documents of Indonesian citizens needs to be improved through comprehensive efforts. There needs to be a better awareness of the importance of immigration documents when outside Indonesia, whether travel documents or residence permit documents in other countries, an understanding of the rights and obligations of migrant citizens, and the criminal acts of not having complete immigration documents.